2016
DOI: 10.1007/s10162-016-0557-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Electrode-Neuron Interface with the Electrically Evoked Compound Action Potential, Electrode Position, and Behavioral Thresholds

Abstract: Variability in speech perception scores among cochlear implant listeners may largely reflect the variable efficacy of implant electrodes to convey stimulus information to the auditory nerve. In the present study, three metrics were applied to assess the quality of the electrode-neuron interface of individual cochlear implant channels: the electrically evoked compound action potential (ECAP), the estimation of electrode position using computerized tomography (CT), and behavioral thresholds using focused stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
137
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 58 publications
14
137
2
3
Order By: Relevance
“…It should be noted that the change in ECAP threshold as the IPG was increased was not significantly related to neural health characteristics. This last finding is in keeping with a recent report by DeVries and colleagues (DeVries, Scheperle, & Bierer, 2016) who reported that ECAP thresholds, but not amplitudes, measured in human subjects were significantly correlated with electrode position within the cochlea (e.g., distance between the electrodes and the modiolus). Taken together, these findings suggest electrode position may significantly contribute to threshold (or near threshold) measures, but measures obtained at higher current stimulation levels reflect, at least in part, neural health.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…It should be noted that the change in ECAP threshold as the IPG was increased was not significantly related to neural health characteristics. This last finding is in keeping with a recent report by DeVries and colleagues (DeVries, Scheperle, & Bierer, 2016) who reported that ECAP thresholds, but not amplitudes, measured in human subjects were significantly correlated with electrode position within the cochlea (e.g., distance between the electrodes and the modiolus). Taken together, these findings suggest electrode position may significantly contribute to threshold (or near threshold) measures, but measures obtained at higher current stimulation levels reflect, at least in part, neural health.…”
Section: Introductionsupporting
confidence: 92%
“…However, it is first important to understand how manipulation of the IPG affects ECAP responses across a multichannel electrode array and if it is feasible to record responses on the majority of electrodes. In deafened human subjects, it is known that both the health of the neural population and the distances from the electrodes to the neurons vary along the length of the cochlea in a subject-specific manner (Nadol, 1997; Long et al, 2014; DeVries et al, 2016). Thus we hypothesized that suprathreshold ECAP measures that reflect cochlear health and or characteristics of the electrode-to-neuron current path would vary along the CI electrode array in a subject specific pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Two CI listeners in particular were selected because they were judged in a previous study (DeVries et al ., 2016) to have poor electrode-neuron interfaces in only the middle frequency region (S43) or the middle and basal frequency regions (S47), somewhat matching those used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…As measured by electrically evoked compound action potential (ECAP), there are data supporting the prediction that a shorter electrode-to-modiolus distance correlates with higher speech recognition score (30). Additionally, there is some evidence that patients with perimodiolar arrays display better speech recognition than those with lateral-wall hugging electrodes (3).…”
Section: Introductionmentioning
confidence: 93%